2015
DOI: 10.1542/peds.2014-1703
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Normalization of Vitamin D Levels: A Meta-Analysis

Abstract: BACKGROUND: Vitamin D deficiency may represent a modifiable risk factor to improve outcome in severe illness. The efficacy of high-dose regimens in rapid normalization of vitamin D levels is uncertain. METHODS:We conducted a systematic review of pediatric clinical trials administering high-dose vitamin D to evaluate 25-hydroxyvitamin D (25[OH]D) response and characteristics associated with final 25(OH)D levels by using Medline, Embase, and the Cochrane Central Register of Controlled Trials, including reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 76 publications
2
70
1
3
Order By: Relevance
“…The highest post-treatment 25(OH)D level was 66.5ng/mL, well below toxic range (88–100ng/mL). 32 The mean baseline VDBP level was almost twice as high in the 66 Hispanic participants compared with the 34 black participants (p<0.001) and did not change with vitamin D3 treatment (Table II). The mean post-treatment serum 25(OH)D level in each of the high-dose arms was in the sufficient range, whereas, the mean post-treatment level in the low-dose arm remained in the deficient range (Figure 2, A).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The highest post-treatment 25(OH)D level was 66.5ng/mL, well below toxic range (88–100ng/mL). 32 The mean baseline VDBP level was almost twice as high in the 66 Hispanic participants compared with the 34 black participants (p<0.001) and did not change with vitamin D3 treatment (Table II). The mean post-treatment serum 25(OH)D level in each of the high-dose arms was in the sufficient range, whereas, the mean post-treatment level in the low-dose arm remained in the deficient range (Figure 2, A).…”
Section: Resultsmentioning
confidence: 91%
“…A meta-analysis for rapid normalization of vitamin D levels (within one month) in pediatric trials found greater efficacy for single or intermittent high-dose loading regimens (≥50,000IU) compared to daily low-dose regimens (1,000–4,000IU) in children and called for more trials studying loading-dose regimens, especially in adolescent patients. 32 Further, they reported an adverse event analysis showing the safety of doses <400,000IU in adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Установлено статистически значимое снижение риска обострения аст-мы (на 59%) при терапии витамином D по сравнению с контролем [28].…”
Section: компенсация дефицита витамина D у детей и подростков при разunclassified
“…По данным боль-шого метаанализа, нагрузочные дозы до 300 000 МЕ (это соответствует, например, двум флаконам Аквадетрима, объем одного флакона -10 мл, в котором содержится 15 000 МЕ витамина D в 1 мл) безопасны в плане гипер-кальциемии или гиперкальциурии: риск этих побочных эффектов повышается при использовании доз более 400 000 МЕ [21].…”
Section: лечение витамин D-дефицитного рахитаunclassified